Optimisation of milling parameter and annealing condition for machining polyetheretherketones (PEEK) biomaterials implant - Aaron, Yu Lung (2017)
Polyetheretherketones (PEEK) which has been widely used in many applications is now commercialized as implant components because of its biodegradability and non-allergic reactions compared to the metal implants. Generally, implants are fabricated by extrusion and injection molding for a larger scale. However, often for prototype designs or patient specific implant designs, it is not economically viable to manufacture by an injection molding. Under such circumstances, it is common to employ a machining process on the PEEK materials to form the components. However, milling parameters are the factors that have to be considered in the machining process to reduce the defects to the minimum and increase its durability. Apart from milling parameters, annealing also plays important roles in reducing residual stress and improving surface finishes. Thus, this research aims to develop exact milling parameters prior to the annealing process for machining PEEK material in order to enhance the machining performance and productivity. To achieve the objective, both statistical and experimental techniques were employed for the methodology. Response surface methods (RSM) were used to get the mathematical models and ANOVA analysis while milling parameters (feed rate, depth of cut and cutting speed) were used in order to get the machining performance on surface roughness, machining force, dimensional accuracy and material removal rate. Through experiments, the optimised parameters have improved the machining performance and qualities prior to the annaeling. The conclusions provide a theoretical basis for the annealing technique where the increased of the percentage crystalline, it helps improving the properties and the materials structure which leads to improve the machinability of the materials. Milling parameters (feed rate, depth of cut and cutting speed) are important factors in machining process and significantly affect the machining performances. To obtain 0.87μm surface finish, unannealed PEEK with 25.3 percentages crystalline will be using cutting speed 150.8 mm/min, feed rate of 0.035mm/tooth and 2mm depth of cut. PEEK annealed with 200°C increase crystalline to 30.3 percentages using high cutting speed (150.8 mm/min), low feed rate (0.033mm/tooth) and low depth of cut (2mm) can produce 0.4μm surface finish. PEEK annealed with 250°C has 30.9 percentages crystalline and 0.39μm surface finish can be obtained by using high cutting speed (150.8 mm/min), low feed rate (0.034mm/tooth) and low depth of cut (2mm). Therefore, milling machining is recommended to be further used in fabricating PEEK biomedical implants.